Perbandingan Pendidikan Islam Internasional dan Global: Kajian Konseptual dalam Konteks Pendidikan Islam Kontemporer - Ayu Watawalaini; Munir Munir; Nurlaila Nurlaila (Jurnal Bilqolam Pendidikan Islam, 2025)
This article aims to examine and compare two forms of contemporary Islamic education development, namely international Islamic education and global Islamic education. This research uses a literature study method using a descriptive qualitative approach, the discussion focuses on the characteristics, scope, curriculum, and use of technology of the two educational models. The results of the study show that international Islamic education emphasises a formal academic system with a global standard curriculum such as Cambridge and IB, while global Islamic education is more flexible and emphasises the spread of Islamic values through non-formal and digital approaches across countries. This comparison is important in facing the challenges of globalisation and the needs of Muslims for quality education rooted in Islamic values.